Meet the mini-mammals : a night at the natural history museum - Stewart, Melissa (Beach Lane Books, 2025)
"Step inside a magical museum... and meet the mini-mammals! These itty bitty beasts may be some of the world's smallest mammals, but they live big, fascinating lives. Come learn about them--and find out which mini-mammal is the teeniest of all"--Provided by publisher.